Korean cinema unleashed = (Korea Foundation, 2006)
This film documents the history and development of Korean filmmaking through these topics: 1. Melodramas: Korean sensibilities; 2. Grand theme of Korean cinema: a nation divided; 3. The artists of Korean cinema.